Meningkatkan Kesadaran Anti-Bullying melalui Bimbingan Kelompok dengan Teknik Sosiodrama pada Siswa SMA Negeri 1 Gedeg Kelas XI IPS - Issac Briyan Alisyahbana; Endang Pudjiastuti Sartinah; Mochamad Nursalim (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2021)
The purpose of this study was to determine the use of sociodrama techniques in increasing anti-bullying awareness of students through group guidance services. This study used action research (Action Research), with 2 cycles, namely cycles I and 2, each meeting two times and each meeting using a time of 1 time 40 minutes. Data collection methods used were observation, interviews, and documentation to determine the level of politeness of students in the implementation of group guidance services in schools. The research subjects were 10 students from school who have problems in their polite behavior. Based on the results of observations of students in cycle I and cycle II, it is known that there has been an increase in the politeness of students which includes good criteria for the implementation of group guidance services using the Sociodrama technique, namely at the meeting after the implementation of cycle 1, there was a change in the behavior of students reaching 63%, which means that in shows the politeness behavior of students in Good Criteria, and at the meeting after cycle 2 there is an increase to 76%, namely in Good criteria. Thus from the results of the analysis it can be concluded that the action research hypothesis which reads